Atmospheric Ray Tracing: An efficient, open-source framework for finding eigenrays in a stratified, moving medium - Schäfer Philipp; Vorländer Michael (Acta Acustica, 2021)
In this paper, an open-source framework for ray tracing in a stratified moving medium is introduced. This framework provides an efficient method to find eigen-rays connecting a source with a receiver and is designed for the purpose of aircraft noise auralization. The method is tested with respect to accuracy and run-time in an aircraft flyover scenario and compared to a state of the art method. The investigation showed that this method provides eigenrays with preset accuracy for source positions most relevant for flyover scenarios and that it is significantly faster than the state of the art method. According to the performance analysis, the presented approach has great potential for integration into future real-time auralizations of aircraft noise.